Continuous monitoring of advanced hemodynamic parameters shows early cardiovascular changes in a cohort of 492 COVID-19 hospitalized patients. (14th October 2021) - Nachman, D; Eisenkraft, A; Maor, Y; Constantini, K; Goldstein, G; Levy, R; Halberthal, M; Horowitz, N A; Golan, R; Rosenberg, E; Lavon, E; Cohen, O; et al.
Abstract: Background: COVID-19 exerts deleterious cardiopulmonary effects, leading to worse prognosis in the most effected. Purpose: The aim of this retrospective multi-center observational cohort study was to analyze the trajectories of key advanced hemodynamic parameters amongst hospitalized COVID-19 patients according to different risk populations using a chest-patch wearable providing continuous remote patient monitoring. Methods: The study was conducted in five COVID-19 isolation units. Patients admitted to the units were connected to a photoplethysmography based noninvasive remote advanced hemodynamic monitor after completing a basic risk factor survey. Physiological parameters were measured every 15 minutes during the hospitalization, including cardiac output (CO), cardiac index (CI), systemic vascular resistance (SVR), heart rate, blood pressure (BP), respiratory rate, blood oxygen saturation (SpO2), and body temperature. Results: 492 COVID-19 patients (179 females, average age 58.7 years) were included in the final analysis, with more than 3 million measurements collected during an average of 75.3 hours. Overall, within the first five days of hospitalizations we found a significant increase in SVR, and a significant decrease in SpO2, DBP, CO and CI (p<0.01 for all). The changes were more prominent in high risk populations- males, older age and obesity and had a temporal correspondence to changes in respiratory parameters. Conclusions: This is the first comprehensive continuous advanced hemodynamic profiling of COVID-19 patients. Worse hemodynamic status was prominent in high risk populations. FUNDunding Acknowledgement: Type of funding sources: None.